2016
DOI: 10.1038/srep24708
|View full text |Cite
|
Sign up to set email alerts
|

Elastase levels and activity are increased in dystrophic muscle and impair myoblast cell survival, proliferation and differentiation

Abstract: In Duchenne muscular dystrophy, progressive loss of muscle tissue is accompanied by fibrosis, chronic inflammation and reduced muscle regenerative capacity. Although much is known about the development of fibrosis and chronic inflammation in muscular dystrophy, less is known about how they are mechanistically linked to loss of muscle regenerative capacity. We have developed a proteomics method to discover dystrophy-associated changes in the muscle progenitor cell niche, which identified serine proteases, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…It is known that neutrophils can cause muscle fiber damage in vitro and in vivo (25) and that oxidants released by these cells can cause severe cellular damage. Recent studies also implicate a role for HNE in muscular dystrophies by impairing myoblast cell survival, proliferation, and differentiation (26). We found that, while NETs do not impair myoblast proliferation, they significantly decrease skeletal myotube viability.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is known that neutrophils can cause muscle fiber damage in vitro and in vivo (25) and that oxidants released by these cells can cause severe cellular damage. Recent studies also implicate a role for HNE in muscular dystrophies by impairing myoblast cell survival, proliferation, and differentiation (26). We found that, while NETs do not impair myoblast proliferation, they significantly decrease skeletal myotube viability.…”
Section: Discussionsupporting
confidence: 53%
“…This is relevant, as biopsies from IIM subjects, but not healthy muscle, displayed evidence of infiltrating netting neutrophils and NET structures. Given the high levels of HNE present in NETs, it is possible that it and other proteases play prominent roles in the induction of myotube cell death (26). However, blocking the effects of HNE did not improve myotube viability, while citrullinated histones recapitulated the toxic effect of NETs on myotube viability.…”
Section: Discussionmentioning
confidence: 99%
“…Altered CA3 levels and its leakage into the circulatory system may be related to fibre type-specific susceptibilities and accompanying changes in the dystrophic phenotype [3]. Consistent changes were also reported for annexin isoforms ANX1, ANX2 and ANX5, which may be related to disturbed Ca 2+ -homeostasis and repair mechanisms within dystrophic fibres [42,45,50,61,64,67,[71][72][73][74]. Potential compensatory mechanisms that are based on the up-regulation of cytoskeletal elements were confirmed by mass spectrometry.…”
Section: Proteomic Profiling Of Dystrophic Skeletal Musclessupporting
confidence: 53%
“…These types of muscle proteins are more appropriately analyzed by one-dimensional gel electrophoretic techniques that can be combined with on-membrane digestion and mass spectrometry [34,43,72,77] or affinity purification and immunoprecipitation approaches [39,41,44,77]. Alternatively, skeletal muscle proteins that are present in crude tissue extracts or subcellular fractions can be conveniently analyzed by bottom-up proteomics, which employs trypsination of total protein complements in combination with liquid chromatography and mass spectrometry [30,45,56,60,62,64,[66][67][68][69]71,[73][74][75][76]78].…”
Section: Proteomic Profiling Of Dystrophic Skeletal Musclesmentioning
confidence: 99%
See 1 more Smart Citation